2015
DOI: 10.1371/journal.pone.0131767
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis and Human Immunodeficiency Virus Type 1 Cooperatively Modulate Macrophage Apoptosis via Toll Like Receptor 2 and Calcium Homeostasis

Abstract: The emergence of drug resistant strains of Mycobacterium tuberculosis (M. tuberculosis) together with reports of co-infections with the human immunodeficiency virus (HIV) has renewed interest to better understand the intricate mechanisms prevalent during co-infections. In this study we report a synergistic effect of M. tuberculosis and HIV-1, and their antigens Rv3416 and Nef, respectively, in inhibiting apoptosis of macrophages. This inhibition involves the TLR2 pathway and second messengers that play complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 36 publications
2
39
0
1
Order By: Relevance
“…The human monocyte-Mf cell line THP-1 was maintained in RPMI-1640 medium supplemented with 10% FBS and 2 mM L-glutamine and was used throughout the study. Consistent with previous reports from our laboratory, THP-1 monocytes were differentiated into Mfs with PMA [9]. Unless otherwise mentioned, cells were stimulated with 15 mg/ml of recombinant Rv3529c, with or without ligands to various TLRs (Pam 3 Csk 4 for TLR2 and LPS for TLR4 at 1 mg/ml, imiquimod for TLR7 at 5 mg/ml, and CpG DNA for TLR9 at 5 mM), each for indicated times.…”
Section: Cell Culture and Stimulationmentioning
confidence: 82%
See 3 more Smart Citations
“…The human monocyte-Mf cell line THP-1 was maintained in RPMI-1640 medium supplemented with 10% FBS and 2 mM L-glutamine and was used throughout the study. Consistent with previous reports from our laboratory, THP-1 monocytes were differentiated into Mfs with PMA [9]. Unless otherwise mentioned, cells were stimulated with 15 mg/ml of recombinant Rv3529c, with or without ligands to various TLRs (Pam 3 Csk 4 for TLR2 and LPS for TLR4 at 1 mg/ml, imiquimod for TLR7 at 5 mg/ml, and CpG DNA for TLR9 at 5 mM), each for indicated times.…”
Section: Cell Culture and Stimulationmentioning
confidence: 82%
“…T4 DNA ligase and ligation buffer (Thermo Fisher Scientific) were used for overnight ligation of the amplicons to the pGEMT and pET28b vector (Sigma-Aldrich). The histidine-tagged protein Rv3529c was purified with Ni-NTA agarose beads (Qiagen) followed laboratory standardized procedures [9,10]. Sequencing of the Rv3529c gene was confirmed after cloning.…”
Section: Cloning and Expression Of Rv3529cmentioning
confidence: 99%
See 2 more Smart Citations
“…It is still unclear how TLR2 influences HIV and MTB infection. Mehto et al [23] reported that MTB and HIV-1 promote apoptosis in macrophages through the TLR2 signal pathway. In addition, Qin et al [24] found that the inhibitory immune reaction of TLR2 is damaged by inducing over-expression of regulatory T-cell (Treg), which causes viral infection.…”
Section: Cd4mentioning
confidence: 99%